Banjir bandang aceh 2025 dan peran pendidikan keluarga islam dalam pembentukan kesadaran ekologis: studi literatur dan netnografi mini pada media sosial - Arrosidah, Fatihatu Khair; Arrosidah, Fatihatu Khair; Arifin, Ihsan Al (Maliki Interdisciplinary Journal, 2026)
The 2025 Aceh flash flood represents an ecological crisis rooted in the interplay between biogeophysical and socio-political factors. Reports from WALHI, media coverage, and citizen documentation show that long-term ecological degradation—including the loss of 1.4 million hectares of forest, land-use change, and weak oversight of extractive industries—significantly contributed to the disaster’s severity. Public criticism on social media further challenges the narrative that the event was purely natural, highlighting governance failures in environmental management. Using literature review and mini-netnography, this article examines the crisis through the lens of Islamic ecotheology, which views environmental destruction as a violation of human responsibility as khalifah fil ardh (stewards of the earth). The study emphasizes the crucial role of Islamic family education in developing ecological awareness from an early age. The internalization of Islamic values such as trust, responsibility, balance, and the prohibition of fasad within the family serves as a long-term preventive strategy to cultivate environmentally conscious generations. The findings affirm that addressing ecological crises requires collaborative efforts among families, schools, communities, and the state to foster sustainable environmental awareness.